Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Prospective intraindividual comparison of gadoterate and gadobutrol for cervical and intracranial contrast-enhanced magnetic resonance angiography - Lang, Stefan; Weibart, Marina; Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Essig, Marco; Kloska, Stephan; Dörfler, Arnd; Hölter, Philip (Neuroradiology, 2017)
PURPOSE: Gadobutrol (GB) is reported to provide improved relaxivity and concentration compared to gadoterate (GT). This study was designed to intraindividually compare quantitative and qualitative enhancement characteristics of GB to GT in cervicocranial magnetic resonance angiography (MRA) of patients with cerebrovascular disease (CVD). METHODS: Patients (n = 54) with CVD underwent two identical contrast-enhanced magnetic resonance angiography (CE-MRA) examinations of the cervical and intracranial vasculature in randomized order, using GB and GT in equimolar dose. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were obtained by two independent neuroradiologists, blinded to the applied contrast agents. Qualitative assessment was performed using a three-point scale with a focus on M1/M2 segments. RESULTS: One thousand and twenty-six vessel segments were analyzed. GB revealed a significantly higher SNR (p = 0.032) and CNR (p = 0.031) in all vessel segments. GB featured a significantly higher SNR and CNR in thoracic (p = 0.022; p = 0.016) and cervical vessels (p = 0.03; p = 0.038), as well as in the posterior circulation (p = 0.012; p = 0.005). In blinded qualitative assessment, overall preference was given to GB (p = 0.02), showing a significant better delineation of the M1/M2 segments (p = 0.041). CONCLUSION: Compared to GT, the use of GB results in a significantly higher SNR and CNR in cervical and cerebral CE-MRA, leading to a better delineation of the intracranial vasculature. Present results underline the potential of GB for improved CE-MRA assessment of vasculature in CVD patients.
EVALuna2:33134

Quiet FLAIR at 7T MRI - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Dörfler, Arnd; Grodzki, David M. (Investigative Radiology, 2020)
OBJECTIVE: The aim of this study was to investigate acoustic noise reduction and image quality of cranial magnetic resonance imaging (MRI) at 7T MRI with and without sequence-based acoustic noise reduction. MATERIALS AND METHODS: Fifteen patients and 5 healthy volunteers underwent 7T MRI scanning. A fluid-attenuated inversion recovery (FLAIR) sequence was acquired with and without sequence-based acoustic noise reduction. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio, contrast-to-noise ratio, lesion conspicuity, level of artifacts, and overall image quality were performed. Furthermore, detection rates of white matter lesions were evaluated by 2 observers for both sequences. RESULTS: Acoustic noise was significantly reduced from initially 92.7 dB(A) to 78.9 dB(A), corresponding to an 80% reduction in sound pressure. The visual assessment revealed no significant difference in the level of artifacts. Although rated very high by both readers, lesion conspicuity and image quality averaged better for the regular FLAIR sequence. Signal-to-noise ratio and contrast-to-noise ratio slightly decreased when applying the sequence-based acoustic noise reduction. No significant difference was found between the detection rates of white matter lesions for both observers. CONCLUSIONS: Reducing sound pressure by 80% in FLAIR imaging at 7T ultra-high-field MRI is feasible while maintaining high diagnostic image quality.
CRIS-Team Scopus Importer:2020-10-23

Standardized acquisition and post-processing of dynamic susceptibility contrast perfusion in patients with brain tumors, cerebrovascular disease and dementia: comparability of post-processing software - Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Larsson, Elna Marie; Nguyen, Than; Essig, Marco; Dörfler, Arnd; Hölter, Philip (British Journal of Radiology, 2020)
OBJECTIVE: MR-perfusion post-processing still lacks standardization. This study evaluates the results of perfusion analysis with two established software solutions in a large series of patients with different diseases when a highly standardized processing workflow is ensured. METHODS: Multicenter data of 260 patients (80 with brain tumors, 124 with cerebrovascular disease and 56 with dementia examined with the same MR protocol) were analyzed. Raw data sets were processed with two software suites: Olea sphere and NordicICE. Group differences were analyzed with paired t-tests and one-way ANOVA. RESULTS: Perfusion metrics were significantly different for all examined diseases in the unaffected brain for both software suites [ratio cortex/white matter left hemisphere: mean transit time (MTT) 0.991 vs 0.847, p < 0.05; relative cerebral bloodflow (rBF) 3.23 vs 4.418, p < 0.001; relative cerebral bloodvolume (rBVc) 2.813 vs 3.884, p < 0.001; right hemisphere: MTT 1.079 vs 0.854, p < 0.05; rBF 3.262 vs 4.378, p < 0.001; rBVc 2.762 vs 3.935, p < 0.001)]. Perfusion results were also significantly different in patients with stroke (ratio cortex/white matter affected hemisphere: MTT 1.058 vs 0.784; p < 0.001), dementia (ratio cortex/white matter left hemisphere: rBVc 1.152 vs 1.795, p < 0.001; right hemisphere: rBVc 1.396 vs 1.662, p < 0.05) and brain tumors (ratio cortex/whole tumor rBVc: 0.778 vs 0.919, p < 0.001 and ratio cortex/tumor hotspot rBVc: 0.529 vs 0.512, p < 0.05). CONCLUSION: Despite a highly standardized workflow, parametric perfusion maps are depended on the chosen software. Radiologists should consider software related variances when using dynamic susceptibility contrast perfusion for clinical imaging and research. ADVANCES IN KNOWLEDGE: This multicenter study compared perfusion parameters calculated by two commercial dynamic susceptibility contrast perfusion post-processing software solutions in different central nervous system disorders with a large sample size and a highly standardized processing workflow. Despite, parametric perfusion maps are depended on the chosen software which impacts clinical imaging and research.
CRIS-Team Scopus Importer:2019-12-24

T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593